Nutritional Programming in Yellow Catfish: Dietary Phaffia rhodozyma Effects on Growth Performance, Antioxidant Capacity, and Intestinal Health - Shengjie Lin; Yaling Wang; Tengyang Lu; Muhammad Jawad; Haijing Xu; Qingwen Zhou; Aimin Wang; Mingyou Li (Fishes, 2026)
The sustainable production of yellow catfish (Pelteobagrus fulvidraco) fry is critical for aquaculture, yet early developmental stages face high mortality and nutritional challenges. This study evaluated the effects of dietary supplementation with broken-cell wall P. rhodozyma on growth performance, organ development, enzyme activities, and gut microbiota composition in yellow catfish fry. Dietary supplementation with broken-cell wall P. rhodozyma significantly improved fry performance, increasing survival from 12% to 52%, promoting growth, enhancing intestinal and liver development, improving digestive enzyme activities, and modulating antioxidant-related physiological responses. It also elevated beneficial Muribaculum and reduced Streptococcus in the gut, promoting microbiota stability. These results demonstrate that P. rhodozyma supplementation not only improves early growth, organ maturation, stress resistance, and intestinal health but also effectively enhances overall fry health and development, thus supporting its use as a functional feed additive in aquaculture.